PENGAWASAN PEREDARAN MINUMAN KERAS ILEGAL OLEH KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TEMBILAHAN - Dira Heriyanti; Mimin Sundari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Indragiri HIlir regency is a fairly wide water territory, and thus it is often used as a route to transport illegal goods such as liquor which are often imported from free territory. There are still many unofficial ports and jetty which are prone to have smuggling activity, and also the difficulty to access the crime scene, thus causing an increase in the number of illegal liquor smuggling from 2017 – 2019. The expensive customs cost of liquor and the lack of firm punishment also cause an increase in the number of illegal liquor smuggling. The goal of this research is to find out how is the illegal liquor distribution control by the customs and excise control and services office in Indragiri HIlir, and also to find out the illegal liquor distribution control inhibition factors. The type of this research is qualitative research, by connecting the primary data with the secondary data. The data are gathered from interview, observation, and documentation, which then are analyzed thus a conclusion to the research problem can be made. This research conclude that the illegal liquor distribution control by the customs and excise control and services office in Indragiri HIlir is not yet optimal, this is caused by several inhibition factors such as the lack of sufficient manpower, insufficient infrastructure such patrol boats which are used to conduct surveillance, limited monetary resources, and the low awareness of the import actors. Keywords : Management, Control, Smuggling